Attentional Skills in Soccer: Evaluating the Involvement of Attention in Executing a Goalkeeping Task in Virtual Reality - Andria Shimi; Vanessa Tsestou; Marios Hadjiaros; Kleanthis Neokleous; Marios Avraamides (Applied Sciences, 2021)
Physical abilities are essential to goalkeepers in soccer but the involved cognitive abilities for these players have only recently become the focus of extensive research. In this study, we investigated the role of different aspects of attention in a basic goalkeeping task in soccer. One hundred participants assumed the role of a goalkeeper in immersive virtual reality (VR) and carried out a task that entailed blocking balls shot towards their goal. In addition, they carried out two computerized tasks each assessing different attentional abilities: the Attention Network Test provided scores for three well-established networks of attention, namely the alerting, the orienting, and the executive control. The Whack-a-Mole task evaluated inhibitory control, by measuring performance in a classic Go/No-Go task and tapping on response inhibition. A regression analysis revealed that all three attention network scores contributed to performance in the VR goalkeeping task. Furthermore, performance in the Whack-a-Mole task correlated significantly with performance in the VR goalkeeping task. Overall, findings confirm that cognitive skills relating to attention play a critical role in the efficient execution of soccer-specific tasks. These findings have important implications for the training of cognitive skills in sports.